A modified strain energy density exhaustion model for creep–fatigue life prediction. (September 2016) - Wang, Run-Zi; Zhang, Xian-Cheng; Tu, Shan-Tung; Zhu, Shun-Peng; Zhang, Cheng-Cheng
Highlights: Energy density exhaustion model for creep-fatigue life prediction is proposed. Mean stress effect is considered in the present model. The present model is more accurate than the existing models. Abstract: The accumulated creep–fatigue damage is expected to be an important failure mechanism for lots of high-temperature components. The aim of this paper is to propose a modified strain energy density exhaustion model to predict the tension-hold-only creep–fatigue life. This model exhibits high accuracy due to the reasonable evaluation of creep damage. The proposed model elaborates the determinations of mean stress, stress relaxation rate and creep damage. A few existing experimental data sets of Grade 91 steel, Alloy 617 and 304 stainless steel are used to verify the prediction capacity of the present model under different temperatures and loading conditions. Results show that most of the experimental data falls into a range within a scatter band of ±1.5 on life.